Impactos domésticos da liberalização comercial: perspectivas do debate sobre comércio nos Estados Unidos - Souza, Guilherme Gonsales Rocca e (2022)
Trump's election marked the return of the protectionism debate in US domestic politics through an "anti-globalization" discourse that promised to make "America great again". However, the globalization criticized by the Republican candidate was largely engineered by U.S. interests from the trade liberalization drive of the 1990s, marked heavily by NAFTA and China's integration into the global economy through the WTO. The trade deepening projects, however, came to coexist with political polarization emergence and strong domestic social pressures from groups that considered themselves "losers" of the globalization process. Thus, this research sought to understand some of the main interpretations about the domestic impacts of the United States' trade policy. In a first moment, the historical trajectory of the NAFTA negotiations is described, highlighting the role of the United States and as well as of the agreement's supporters and critics. Then, we present the main ideas that supported the creation of NAFTA and the subsequent trade expansion, as well as its main criticisms. Next, we systematize some studies on the economic impacts of NAFTA, followed by an analysis of Trump's criticism of this project and the critical interpretations on how the liberalizing impulse responded to the interests of the American capital. In a second moment, we sought to describe the historical trajectory of the Uruguay Round negotiations and the PNTR status for China, which paved the way for the country's accession to the WTO